Design a sustainable micro-mobility future: trends and challenges in the US and EU. (2nd September 2022) - Avetisyan, Lilit; Zhang, Chengxin; Bai, Sue; Moradi Pari, Ehsan; Feng, Fred; Bao, Shan; Zhou, Feng
ABSTRACT: Micro-mobility is promising to contribute to sustainable cities with its efficiency and low cost. To better design such a sustainable future, it is necessary to understand the trends and challenges. Thus, we examined people's opinions on micro-mobility in the US and the EU using Tweets. We used topic modelling based on advanced natural language processing techniques and categorised the data into seven topics: promotion and service, mobility, technical features, acceptance, recreation, infrastructure and regulations. Furthermore, using sentiment analysis, we investigated people's positive and negative attitudes towards specific aspects of these topics and compared the patterns of the trends and challenges in the US and the EU. We found that (1) promotion and service included the majority of Twitter discussions in the both regions, (2) the EU had more positive opinions than the US, (3) micro-mobility devices were more widely used for utilitarian mobility and recreational purposes in the EU than in the US and (4) compared to the EU, people in the US had many more concerns related to infrastructure and regulation issues. These findings help us design and prioritise micro-mobility to improve their safety and experience across the two areas for designing a more sustainable micro-mobility future.